Frequency of cervical spine injuries in patients with midface fractures. Issue 1 (January 2020) - Färkkilä, E.M.; Peacock, Z.S.; Tannyhill, R.J.; Petrovick, L.; Gervasini, A.; Velmahos, G.C.; Kaban, L.B.
Abstract: The aim of this retrospective cohort study was to determine the frequency and risk factors for cervical spine injury (CSI) in patients with midface fractures. Patients ≥18 years of age entered in the Massachusetts General Hospital Trauma Registry from 2007 to 2017 were identified. Those with a midface fracture, computed tomography and/or magnetic resonance imaging of the cervical spine, and complete medical records were included. There were 23, 394 patients in the registry; 3950 (16.9%) had craniomaxillofacial fractures and 1822 (7.8%) had a CSI. Craniomaxillofacial fractures included fractures of the midface ( n  = 2803, 71.0%), mandible ( n  = 873, 22.1%), and midface plus mandible ( n  = 274, 6.9%). The overall frequency of CSI in patients with midface fractures was 11.4% (350/3077). Patients with midface fractures had a higher risk for CSI compared to patients without a midface fracture (odds ratio 2.4, 95% confidence interval 2.1–2.4, P  < 0.001). In a multivariate model, nasal and orbital fractures, chest injuries, age, injury severity score, and motor vehicle crash or fall as the etiology were independent risk factors for CSI. Mortality was two times higher in subjects with CSI. Early and accurate diagnosis of CSI is a critical factor when planning the treatment of patients with these fractures.